(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
(e.g. pyramidal sequences) on the performance of mine haulage drifts (e.g. ore access units), the tonnage of unmined ore at risk, and the required quantity of fill material. Using RS2D software, a two-dimensional, elasto-plastic finite-element model for a haulage drift located at 1200m below the surface in the orebody’s footwall has been built. The spread of yielding zones into the rock mass around an access drift and unmined stopes is used to assess mine haulage drift stability and estimate the amount of unmined ore at risk owing to local mining activity. The findings are presented and discussed in terms of the size of failure zones, the number of tonnes of unmined blocks at risk, and the amount of backfill materials required, all in relation to the mining stage. The findings show that haulage drift stability is rapidly diminishing. The drift roof begins to deteriorate at an early stage (after mining step 3). In the drift roof, left wall, floor, and right wall, failure zones measured 1.55m (step 3), 2.28m (step 4), 2.57m (step 5) and 1.88m (step 5) accordingly. After mining step 4, there was a total of 905 m3 of unmined ore at risk (4100 tons), and after mining step 5, a total of 1500 m3 (30 tons) of back fill material was required to strengthen stopes.